Determinan Kerusakan Lingkungan di Provinsi Indonesia dengan Tingkat Tercemar Paling Tinggi - Wahyu Aji Wijaya; Khoirul An’am; Romualdus T.P Maro Djanggo (Indo Publishing, 2025)
In this era, environmental degradation can no longer be ignored. Concerns about extreme climate change and global warming caused by greenhouse gas emissions are growing. The primary drivers of climate change are increased human activity driven by increased industrialization, rising global population growth, and the need to adapt to these changes. Human activity that causes carbon dioxide emissions comes from fossil fuels and deforestation. The data analysis technique used in this study is panel data regression estimation with a cross-section of 22 provinces in Indonesia for the period 2018-2023. The findings of this study conclude that economic growth, energy consumption, and forest area significantly influence carbon dioxide emissions in Singapore, Japan, Israel, South Korea, the United Arab Emirates, and Saudi Arabia from 2001-2020. The results show that forest area and economic growth have a positive and significant relationship with CO2 emissions across all provinces in Indonesia. This means that increasing forest area and economic growth actually contribute to increased emissions, due to increased exploitation of natural resources and industrialization. On the other hand, electricity consumption has a negative and significant relationship with CO2 emissions, indicating that increasing the use of electricity from renewable energy sources actually helps reduce emissions. Meanwhile, urban population growth has no significant effect on CO2 emissions, indicating that urbanization does not directly increase carbon pollution. These findings emphasize the importance of sustainable development policies that prioritize clean energy and responsible forest management across all provinces in Indonesia to balance economic growth with efforts to control climate change.